O mal sofrido em Paul Ricoeur - Machado, Adriane da Silva (2009)
This is a study of the hardship suffered in Paul Ricoeur. Ricoeur believes that one of the greatest confusion pertains to the problem of evil is to put under the same optical phenomena as diverse as sin and suffering. Thus, this work tries to highlight the distinction made by the author of evil committed (sin) and the hardship suffered (suffering). For this purpose, it was necessary to conceptualize the harm in Ricoeur and then addressing the concept of harm suffered. For Ricoeur, the evil has not been the causative agent, to the extent that the suffering challenges us, hitting us indiscriminately. Finally, it is suggested that the wording of the evil is always unsatisfactory and therefore you must rescue the foundation of evil by an ethic that reflects from the set.